ANALISIS PERBANDINGAN PEMEROLEHAN BAHASA ANAK PEREMPUAN DAN LAKI-LAKI USIA 2 TAHUN PADA ASPEK FONOLOGI - Nurmaula Syafa; Dita Rahmanianti; Neni Triyani; Mekar Ismayani (IKIP Siliwangi, 2018)
This study discusses the comparison the language acquisition of two years old different gender. The purpose of this study is to find out the utterances spoken by two children in the phonological aspect. This subject research is one boy and one girl, the age of both are two years old who is in research anvironment.the kind of this research use descriptive qualitative,because this research to show the result of research based on the fact that exist is empirically alive to the speakers the language acquisition process in childrens’ phonological aspects. the technique used to collect data by method of research pointing some picture of animal and fruit and make effort so that both of the child are mentioned the picture that have been provided by reserachers. After obtaining the data, then the data transcrioptioned into the written and the table that the researchers easly to review ing and describing change in phonemes uttered by both of child. The result of this research to show that from 20 speech of utterances by child two years old are sampled in this research, the change of sounds more likely occur in girl than boys. It can be seen from the result data of research that the boy is able to say (Cicak) clearly, while for girl when she says the word (Cicak) is only able to pronounce the end of vocabulary become (cak). The conclusion obtain is the process of language acquisition can be ionfluenced by gender.